2001
DOI: 10.1046/j.1432-1327.2001.02165.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the cDNA and gene for human epitheliasin

Abstract: Previously, we reported cloning and characterization of the mouse gene, epitheliasin. In the present work we cloned the cDNA of the full‐length human orthologue and characterized its gene including 2 kb of 5′ flanking sequence. Analysis of epitheliasin gene expression in adult tissues shows that it is expressed as 3.4 kb and 2 kb transcripts. The major 3.4 kb transcript is observed in the following order: prostate > colon > small intestine > pancreas > kidney > lung > liver. Epitheliasin transcripts in fetal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 46 publications
1
54
0
1
Order By: Relevance
“…Cells-To first decipher the consequences of the reduction of DHT glucuronidation on the cellular response to androgens, the mRNA levels of eight androgen-regulated genes were compared in control and UGT-deficient LNCaP cells cultured in the presence or absence of 1 nM concentration of R1881 and DHT for 12 h. As illustrated in Table 3, this set of genes (six up-regulated: PSA, KLK4, NKX3.1, SLC16A6, TMPRSS2, and VEGF; two down-regulated: ABCG1 and RAD23A) was chosen based on previous studies having reported the androgen-dependent regulation of their expression in LNCaP cells (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). As expected, the two AR agonists induced PSA, KLK4, NKX3.1, SLC16A6, and TMPRSS2 transcript levels in control cells, whereas VEGF expression was only significantly stimulated by R1881 (Fig.…”
Section: Inhibition Of Ugt2b15/b17 Enhances the Androgen Signaling Pamentioning
confidence: 99%
“…Cells-To first decipher the consequences of the reduction of DHT glucuronidation on the cellular response to androgens, the mRNA levels of eight androgen-regulated genes were compared in control and UGT-deficient LNCaP cells cultured in the presence or absence of 1 nM concentration of R1881 and DHT for 12 h. As illustrated in Table 3, this set of genes (six up-regulated: PSA, KLK4, NKX3.1, SLC16A6, TMPRSS2, and VEGF; two down-regulated: ABCG1 and RAD23A) was chosen based on previous studies having reported the androgen-dependent regulation of their expression in LNCaP cells (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). As expected, the two AR agonists induced PSA, KLK4, NKX3.1, SLC16A6, and TMPRSS2 transcript levels in control cells, whereas VEGF expression was only significantly stimulated by R1881 (Fig.…”
Section: Inhibition Of Ugt2b15/b17 Enhances the Androgen Signaling Pamentioning
confidence: 99%
“…The human TMPRSS2 gene comprises 14 exons and is located on chromosome 21q22.2 (21,35). The murine Tmprss2 orthologue, also known as epitheliasin, encompasses 14 exons on chromosome 16C4 (20).…”
mentioning
confidence: 99%
“…In addition to the fulllength TMPRSS2 protein, analyses of extracts from tissues and cell lines demonstrate an ϳ32-kDa polypeptide consistent with the free serine protease domain of TMPRSS2 that results from autoactivated proteolytic cleavage (1). TMPRSS2 is expressed in several human tissues that comprise large populations of epithelial cells (21), with the highest level of transcripts measured in the prostate gland (27). In accord with the human tissue distribution, the mouse prostate and kidney exhibit the highest level of Tmprss2 expression (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 TMPRSS2, which encodes a serine protease with a transmembrane domain, 7 is highly expressed in both normal and neoplastic prostate epithelium, 8,9 and its expression in prostate cancer cells is androgen-regulated. 8,10 In prostate tumors harboring rearrangements, most frequently the non-coding first exon of TMPRSS2 has been found fused to the fourth exon of ERG in the expressed transcript. The rearrangement thereby places ERG under the androgen-regulated transcriptional control of TMPRSS2.…”
mentioning
confidence: 99%